2020
DOI: 10.1177/2374373520932735
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Perspectives of Canadian Men Diagnosed With Prostate Cancer and Health Care Professionals About Active Surveillance

Abstract: Active surveillance (AS) has gained acceptance as a primary management approach for patients diagnosed with low-risk prostate cancer (PC). In this qualitative study, we compared perspectives between patients and health care professionals (HCP) to identify what may contribute to patient–provider discordance, influence patient decision-making, and interfere with the uptake of AS. We performed a systematic comparison of perspectives about AS reported from focus groups with men eligible for AS (7 groups, N = 52) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…"I got all this information that would cover everybody that ever had prostate cancer, but it was not specific to me." -Participant, 62 years (Lee et al, 2015) Several studies reported unique informational and decision support needs for men on AS (Anderson et al, 2013;Fitch et al, 2017Fitch et al, , 2020Le et al, 2016;Loeb et al, 2018;Mallapareddi et al, 2016;O'Callaghan et al, 2014;Seaman et al, 2019). Men diagnosed with low-risk PCa described the emotional weight of the decision to undergo AS or commence treatment and how the information provided to them by HCPs was rarely empowering enough to make an informed decision.…”
Section: Informational and Decision Support Needsmentioning
confidence: 99%
“…"I got all this information that would cover everybody that ever had prostate cancer, but it was not specific to me." -Participant, 62 years (Lee et al, 2015) Several studies reported unique informational and decision support needs for men on AS (Anderson et al, 2013;Fitch et al, 2017Fitch et al, , 2020Le et al, 2016;Loeb et al, 2018;Mallapareddi et al, 2016;O'Callaghan et al, 2014;Seaman et al, 2019). Men diagnosed with low-risk PCa described the emotional weight of the decision to undergo AS or commence treatment and how the information provided to them by HCPs was rarely empowering enough to make an informed decision.…”
Section: Informational and Decision Support Needsmentioning
confidence: 99%
“…19,20 While a clinician's recommendation is the most important factor in influencing a patient's decision to undergo active surveillance, 21,22 patients may also be unaware of conservative management options, or have difficulty understanding and weighing up treatment options. [22][23][24][25] The thought of not removing the cancer may also provoke fear of cancer growth and metastasis, which may contribute to decisions to opt out from active surveillance once started. 13 Given these significant patient and clinician barriers, effective strategies are needed to promote acceptance of active surveillance for men with low-risk lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Clinicians may not recommend active surveillance to patients because of a patient's clinical and personal characteristics (e.g., younger age), and perceptions of: patient disinterest, inadequacy of biopsy sampling, inconsistency in active surveillance guidelines, and inability of some patients to adhere to follow‐up protocols 19,20 . While a clinician's recommendation is the most important factor in influencing a patient's decision to undergo active surveillance, 21,22 patients may also be unaware of conservative management options, or have difficulty understanding and weighing up treatment options 22–25 . The thought of not removing the cancer may also provoke fear of cancer growth and metastasis, which may contribute to decisions to opt out from active surveillance once started 13 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to quantitative research, a call has been made encouraging qualitative approaches to better understand this issue [ 13 , 14 ]. Existing research highlights the roles of physicians and patients at the time of making treatment decisions, and how their perspectives often differ [ 15 ]. Scherr et al found that treatment decision-making among patients with low-risk PCa was dominated by physicians’ recommendations (mostly based on clinical factors), whereas patients’ preferences were overlooked [ 16 ].…”
Section: Introductionmentioning
confidence: 99%